Portosystemic shunts and refractory hepatic encephalopathy: patient selection and current options - Philips CA (Dove Medical Press, 2019)
Cyriac Abby Philips, Sasidharan Rajesh, Philip Augustine, Guruprasad Padsalgi, Rizwan Ahamed The Liver Unit, Cochin Gastroenterology Group, Ernakulam Medical Centre, Cochin, Kerala, India Abstract: Portosystemic shunt (PS) syndrome encompasses a spectrum of disease manifestations ranging from asymptomatic portal hypertension to recurrent and refractory hepatic encephalopathy, ultimately culminating in progressive hepatic failure in patients of cirrhosis and associated large PSs. PSs commonly seen in cirrhosis include splenorenal, gastrorenal, and dilated paraumbilical veins, all of which can present with recurrent or refractory hepatic encephalopathy. In this exhaustive review, we describe the anatomy of PSs, elucidate new theories on their pathophysiology, discuss the clinical implications of PSs in cirrhosis, provide details on different techniques (classical and novel) of shunt embolization, and explore all the pertinent current literature on shunt embolization for refractory and recurrent hepatic encephalopathy, all of which are enumerated with extensive images and illustrations. Keywords: portosystemic shunts, hepatic encephalopathy, cirrhosis, portal hypertension, embolization, shunt occlusion